Sobre a construção ir a + infinitivo em português europeu - Cunha, Luís Filipe (2022)
Differently from e.g. Spanish, European Portuguese has two analogous but quite independent constructions incorporating the verb ir (to go) that point to the future realisation of an eventuality. In both cases, ir may retain most of its lexical properties or it may arise in constructions that have undergone a lower or greater degree of grammaticalization. The main goal of this paper is to compare the behaviour of these two structures, namely ir ('go') + Infinitive, which consistently conveys a temporal relation of posteriority, and its ir ('go') a + Infinitive counterpart, which seems to carry aspectual information of prospectivity. As a temporal operator, ir ('go') + Infinitive combines with all kinds of eventualities and occurs with different prospective temporal adverbials; on the other hand, as an aspectual operator establishing a preliminary state, ir ('go') a + Infinitive is completely incompatible with statives, is anomalous with long distance future temporal adverbials and demands the presence of another event in order to ensure the requirement of "present relevance".